Analysis of Community Empowerment Through the Development of Potential and Marketing of Tourism Villages - Yusuf, Muhammad; Amirullah, Amirullah; Rusdi, Muh. (Program Pascasarjana Universitas Negeri Makassar, 2024)
Tompo Bulu Village, located on the slopes of Mount Bulusaraung, is a village bordering Maros Regency, especially Camba District, and is part of the Bantimurung-Bulusaraung National Park area. Tompo Bulu is one of the villages that has been designated as a tourist village with a variety of tourism potential but has not been maximally utilised in accordance with community expectations. This research aims to find out: (1) how the community empowerment of Tompo Bulu tourism village in Pangkep Regency; and (2) how the marketing of Tompo Bulu tourism village in Pangkep Regency. This research is an applied research with a qualitative approach and the data is analysed descriptively. The results showed that the community empowerment of Tompo Bulu Tourism Village has not been maximised because the understanding and benefits of tourism village development have not been imprinted on the community. The promotion strategy carried out has used social media which has been widespread. However, because the facilities to the location of the tourist village are not good, the implication is that the encouragement of the wider community to visit the village is lacking.